Learning Curve in External DCR – A Trainee’s Perspective - Bhatia, Karan; Sengupta, Sabyasachi; Bhadauria, Madhu (Nepalese Journal of Ophthalmology, 2018)
Purpose: The aim of this study is to determine the success rate over time in patients undergoing External Dacryocystorhinostomy (DCR) with acquired naso-lacrimal duct obstruction (NLDO), when done by a trainee ophthalmologist.Methods: The study was Prospective Observational study and was conducted in Tertiary Eye Hospital, Uttar Pradesh, India. One hundred and fourteen consecutive adult patients underwent external DCR for acquired complete NLDO by a trainee with less than 3 years of experience in ophthalmology between November 2011 and March 2013. Postoperative anatomic success rate was determined at 6 months on the basis of the patency of lacrimal sac syringing and patients were asked to subjectively evaluate improvement of their epiphora using a questionnaire.Results: Anatomical success rate across the entire study period was 93.7% and this improved from 87% in the first tertile of 38 patients to 94% in the second tertile and 100% in the final tertile of cases (p